Mapping of a Major QTL for Ceratocystis Wilt Disease in an F1 Population of Theobroma cacao - Fernandes, Luciel dos Santos; Royaert, Stefan; Corrêa, Fábio M.; Mustiga, Guiliana M.; Marelli, Jean-Philippe; Corrêa, Ronan X.; Motamayor, Juan C. (Frontiers in Plant Science, 2018)
Cacao is an important crop, its beans are key raw materials for the chocolate and cosmetic industries. Ceratocystis wilt of cacao (CWC) caused by Ceratocystis cacaofunesta is a lethal disease for the crop. Therefore, the selection of resistant cacao varieties is one of the viable ways to minimize losses in cacao production. In this paper, we described the identification of a major QTL associated with CWC in an F1 mapping population from a cross between a resistant, ‘TSH 1188’, and a susceptible genotype, ‘CCN 51’. A set of 266 trees were genotyped using 3526 single nucleotide polymorphic markers and then performed multiple QTL mapping analyses. Two QTLs were identified on chromosomes IV and VI. The major QTL was located at 20 cM from the top position of chromosome VI, accounting for more than 60% of the phenotypic variation. The favorable allele T1, with haplotype GTT, came from the ‘TSH 1188’ parent. It was evident that the haplotype combination T1C2 on chromosome VI was the most significant for resistance, since 93% of resistant trees had this haplotype. The major QTL converged to a genomic region of 739.4 kb that harbored nine candidate genes, including two major classes of resistance genes, which would make them the primary candidates involved in the resistance to CWC. The haplotypes detected are now used to improve the efficiency and precision of the selection of resistant trees in cacao breeding.